Microbe–Host Interactions are Positively and Negatively Regulated by Galectin–Glycan Interactions - Baum, Linda G.; Garner, Omai B.; Schaefer, Katrin; Lee, Benhur (Frontiers in Immunology, 2014)
Microbe-host interactions are complex processes that are directly and indirectly regulated by a variety of factors, including microbe presentation of specific molecular signatures on the microbial surface, as well as host cell presentation of receptors that recognize these pathogen signatures. Cell surface glycans are one important class of microbial signatures that are recognized by a variety of host cell lectins. Host cell lectins that recognize microbial glycans include members of the galectin family of lectins that recognize specific glycan ligands on viruses, bacteria, fungi and parasites. In this review, we will discuss the ways that the interactions of microbial glycans with host cell galectins positively and negatively regulate pathogen attachment, invasion and survival, as well as regulate host responses that mitigate microbial pathogenesis.